Unveiling the putative porcine myosin-based peptide markers for nonhalal meat through chemometrics-assisted MRM-based proteomics - Yuswan, Mohd Hafis; Ali, Norazlina; Ismail, Syaiful Izwan; Abdullah Sani, Muhamad Shirwan; Lai, Kok Song (Springer Nature, 2025)
Handling massive proteomics datasets poses challenges due to assessing dataset quality and dealing with multiple dimensions of the dataset when establishing putative peptide markers. Therefore, this study aims to confirm putative porcine peptide markers for precision halal proteomics through chemometrics-assisted MRM-based proteomics. Chemometric data mining was employed to access the dispersion characteristics and normality of 509 commercial processed meat samples (beef, chicken, fish, and pork). All the samples displayed normal distributions and showed significant differences in the median. By employing chemometric principal component analysis, two significant dimensions were identified to select the putative porcine peptide markers. Out of 1204 identified peptides, two putative porcine peptide markers were critically selected: P25 and P68, derived from myosin-1. MRM acquisition was developed to verify the P25 and P68 for precision halal proteomics. Notably, only the MRM chromatogram of P68 showed a modified peptide peak. Nonetheless, the process of confirming putative porcine peptide markers from massive proteomics datasets is robust and reliable through chemometrics-assisted MRM-based proteomics for halal authentication in the context of meat speciation. It is recommended utilizing P25 as the peptide marker due to its purity and unmatched sequence with bovine, chicken, and fish based on the UniProtKB search